Repositioning of The Modern Market to The Existence of The People's Market - Syafa’at Anugrah Pradana; Dirga Achmad; Azlan Thamrin (Jurnal Mulawarman Law Review, 2024)
The quantity of Modern Markets in Bone Regency has increased sharply, this has an impact on the existence of the people's market. Thus, this study aims to analyze the arrangement of modern markets to restore the existence of the people's market in Bone Regency. The research method used is legal research with a legislative and socio-legal approach. The results obtained are first, the number of modern markets that exceed the number of people's markets in Bone Regency is a sign that the people's markets in Bone Regency are increasingly degraded. Second, when viewed from legal aspects, both philosophical, sociological, and juridical, the people's market needs to be preserved because the people's market is a local wisdom owned by the Indonesian people which has been regulated in Permendag Number 21 of 2021 concerning Guidelines for the Development and Management of Trade Facilities. Therefore, the author suggests that local governments need to establish a regulation related to modern market structuring to restore the dignity of the people's market through regional rules.